What Do You Do When The Law Doesn’t Work? Adult Educators’ Role In Fighting Workplace Discrimination - Ann Brooks; Tamara Clunis (Adult Education Research Conference, 2006)
An analysis of research suggests that ethnic/racial group members lack informal access to developmental opportunities in the workplace. Legal scholars critique Title VII law as ineffective in current organizations. Research shows the work of adult educators is critical in fighting discrimination in the absence of effective legal protection.
Keywords: workplace; discrimination; ethnicity; race